Seqdev: an algorithm for constructing genetic elements using comparative assembly - Rahman, Tasnim; Heickal, Hasnain; Tabrejee, Shamira; Chowdhury, Md Miraj Kobad; Sarwar, Sheikh Muhammad; Shoyaib, Mohammad (© 2016 Bangladesh Association for Plant Tissue, 2017)
This article was published in Plant Tissue Culture and Biotechnology [© 2016, Bangladesh Association for Plant Tissue] and the definite version is available at: http://dx.doi.org/10.3329/ptcb.v26i1.29772. The Journal's website is at: http://www.banglajol.info/index.php/PTCB/article/view/29772